Relationship of emotional intelligence with organizational citizenship behavior among bank employees in Malaysia - Anwar, Md. Aftab; Gani, AAhad M. Osman; Fontaine, Rodrigue Ancelot Harvey (2016)
Organizational citizenship behavior (OCB) exists among employees who have inner feelings of having better work experiences by using their emotional experiences, and also for nurturing these by creating meaningful ethical work environments. These phenomena have not been sufficiently studied especially in the context of recent corporate scandals and ethical violations. Although some studies were conducted on emotional intelligence in the western hemisphere, almost no empirical study was found to have conducted in the Asian context particularly in the competitive banking industry. To bridge the research gap, this study attempted to identify the effects of emotional intelligence (EI) and its underlying dimensions on organizational citizenship behaviour (OCB) of employees working in commercial banks of Malaysia. The findings indicated significant positive impacts of employees’ emotional intelligence and its specific dimensions on OCB. This empirical study found that only self-emotional awareness dimension of EI did not have statistically significant relationship with OCB, but other three dimensions of EI have significant positive relationships with OCB. Bank management should consider developing employees’ emotional intelligence being an integral part for banking industry where employee performance and organizational effectiveness are highly associated with employee citizenship behaviour. Implications of the findings for HRD research and practice are discussed at the end. Recommendations are also made for developing appropriate HRD interventions for improving EI dimensions of employees, and thereby enhancing organizational performance.